Theory of sporting technique and «semantics of motions» - in search of co-operation - Dmitriev S.V.; Mikhaylov Y.A. (Fizičeskoe Vospitanie Studentov, 2010)
Technology of the educational teaching motive actions is examined in a theory and practice of shotput. The biomechanics and psychological semantic mechanisms of organization of motions of pushrod of kernel are investigational. The methods of registration of electric activity of basic muscular groups of sportsmen of different qualification were used. Developed concept-terminology and methodological vehicle of research. It allows to perfect professionally-pedagogical credo of researchers.